Validação de um código baseado no método de elementos finitos utilizado para simular escoamentos incompressíveis - Bragato Junior, Renato (2016)
This paper proposes a validation for a numeric code, written in Fortran language, based on the Finite Element Method used to simulate incompressible fluid flows. Because it is a validation, experimental data were obtained. For such, experiments on the wind tunnel of the UTFPR – Câmpus Pato Branco – PR, were made with the purpose of obtain data to be able to compare with the results of the numeric simulations. During the experimental step, two test bodies were used, a circular cross-section cylinder and a Clark-Y. The cylinder was tested in five different flow conditions, and two of these conditions, the ones that references were found in the literature, were used for the validations of the code. The Clark-Y was tested in tree different velocities and with four different angles of attack, totalizing twelve distinct flow conditions. Based on the fact that no reference data for the Clark-Y were found in the literature, the experiments of the Clark-Y were made to enrich the experimental data of the profile, which has very little about it in the literature. For the numeric simulations, cylinder meshs with 440 and 1146 elements each were used, in the same initial conditions used on the experiments and that were found in the literature, managing to compare the profiles of pressure, between the experiments, the simulation results and the literature, enabling the validation of the code.